Gender Participation in Tertiary STEM Education in Nigeria: Examining the Current Perspectives - Akintoye, Hakeem; Lameed, Soladoye Nurudeen; Bankole, Isaac Sewanu; Adam, Umar Ayotunde; Ayodeji, Benjamin (Journal of Educational Sciences, 2024)
There are global challenges and problems that require sound and prompt knowledge of STEM in order to seek redress. Dearth of individuals with kin knowledge in STEM fields will further pose threat to the survival of nations of the world. Hence, the study looks into gender participation of undergraduate students in tertiary STEM education. 225 (128 males, 97 females) undergraduate students undertaking STEM related courses formed the sample of this study across four Nigerian universities in Lagos State, South West Nigeria using survey design method. Data were collected through the use of self-developed questionnaire. One research question and one hypothesis were answered and tested using inferential statistics of analysis of variance (ANOVA). The findings indicate wide gender gap in participation exists among undergraduate students in tertiary STEM, especially in science, technology and engineering related courses. The finding further reveals a significant difference in gender participation of undergraduate students in tertiary STEM. The study therefore, recommends all stake holders to adopt scholarships and provision of education materials as motivation to attract boys and girls into STEM fields of study.